1994
DOI: 10.1128/aac.38.8.1803
|View full text |Cite
|
Sign up to set email alerts
|

Activity of epiroprim (Ro 11-8958), a dihydrofolate reductase inhibitor, alone and in combination with dapsone against Toxoplasma gondii

Abstract: We examined the effect of epiroprim (Ro 11-8958), a dihydrofolate reductase inhibitor, alone and in combination with dapsone, against Toxoplasma gondii. In vitro, the anti-T. gondii effects of epiroprim and dapsone were observed at nanogram-per-milliliter levels when a 72-h uracil assay and an infection rate of one parasite per 120 macrophages were used. In combination, these drugs exerted a synergistic effect that, however, was only parasitostatic. In a model of acute infection, mice were infected intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…There is clearly a need to develop new, effective combinations against both infections. Several experimental studies performed in vitro and in vivo have shown that PS-15, a new biguanide, and epiroprim (EPI), an analog of TMP, were effective against both P. carinii (7,8,15,26) and T. gondii (6,20) and that they might be good candidates for alternative therapy or prophylaxis. However, these results were obtained in experimental models of single infection and did not take account of the frequent association of these infections in AIDS patients.…”
mentioning
confidence: 99%
“…There is clearly a need to develop new, effective combinations against both infections. Several experimental studies performed in vitro and in vivo have shown that PS-15, a new biguanide, and epiroprim (EPI), an analog of TMP, were effective against both P. carinii (7,8,15,26) and T. gondii (6,20) and that they might be good candidates for alternative therapy or prophylaxis. However, these results were obtained in experimental models of single infection and did not take account of the frequent association of these infections in AIDS patients.…”
mentioning
confidence: 99%
“…Brodimoprim combined with dapsone was active in vitro and in vivo against some mycobacteria (5). Epiroprim combined with dapsone had promising activity in vitro and in vivo against Toxoplasma gondii (1).…”
mentioning
confidence: 99%
“…The EPM-DDS combination was highly active in these models, and the drugs showed synergistic activity in vivo. The combination of EPM with DDS, which has already been demonstrated to have good in vivo activity against opportunistic infections caused by P. carinii (9,14) and Toxoplasma gondii (3,9), also shows activity against a broad range of bacteria causing respiratory tract infections. It is also likely that most atypical mycobacteria, which cause systemic infections once the CD4-cell count drops to Ͻ200/mm 3 , would be inhibited at concentrations achievable in biological fluids.…”
Section: Resultsmentioning
confidence: 99%
“…1), which is considerably more active than TMP against the DHFR from P. carinii isolates but which is not active against the human DHFR (11,12). The combination of EPM with dapsone (DDS), which is also used alone for the prophylaxis of P. carinii pneumonia (7), was highly effective against P. carinii isolates in rats (9,14) and against toxoplasmosis in mice (3,9) and in a model of mixed Pneumocystis and Toxoplasma infection (2). Since both EPM and DDS exhibit high levels of antibacterial activity, we investigated the activities of these compounds, alone and in combination, against a wide range of bacteria in comparison with those of TMP-SMZ and several other agents.…”
mentioning
confidence: 99%